المواطنة والهوية: انتساب جغرافي وانتماء ثقافي - أمين، رافد أحمد محمد; الكريم، اياد رشيد محمد (جامعة تكريت - كلية التربية للعلوم الإنسانية, 2019)
Citizenship is the affiliation of a geographical place that is accompanied by identity as a cultural identity, and citizenship is the attachment to a particular land, but the identity itself and its precise meaning are belonging to certain believes, values and standards, and the dialectical relationship between them (citizenship and identity) strongly indicates that identity is always inherent to citizenship. Citizens in all circumstances and in any geography of an integrated political system supported by economic capabilities and social systems, as well as the laws that regulate the rhythm of those relations, all these points remain on the values and standards (as we have stated), in the sense of a clear identity. The homeland in which individuals live in does not specify the type of identity to which they belong. The one country may be subjected to many changes depending on the different contradictory political systems, and here the identity is the lens through which citizens determine what is appropriate or inappropriate. It is not valid for their homeland, and if the lenses are differed, the evaluation of the persons will differed also as to what they looked at and agreed on the sensory facts. According to this logic, citizens, regardless of their loyalty to their country and their interest in their interests, cannot view that interest as citizens only, but must look at it according to their hobbies. Therefore, the citizens must have an identity and a culture that is the vision they see to reality and the standard in which they propose solutions to their problems, and citizenship in one country will be fragile if it has multiple identities and may lead to fragmentation, and in the case of the possibility of unification of identities in one country necessarily leads to the construction of a strong one and true citizenship, meaning that the different in the same country because of multiple identities must meet to determine the principle. Then they need to look at how they are achieving this goal, and on the basis of their in-depth understanding of the fact: "These are our situations and our differences. Let us look for a genuine and proportionate solution, which necessarily requires some concessions and compromises. "We will discuss the subject through two studies: First: Citizenship, national affiliation and integration.
المواطنة: هي الانتساب لرقعة جغرافية ترافقها الهوية كانتماء ثقافي، والمواطنة بذلك تكون الالتصاق بأرض معينة، لكن الهوية بحد ذاتها وبمفهومها الدقيق هي انتماء إلى معتقدات وقيم ومعايير معينة، والعلاقة الجدلية التي تربطهما (المواطنة والهوية) بقوة تشير إلى أن الهوية ملازمة دائما للمواطنة، ولا بد للمواطنين في كل الظروف وفي أي جغرافية من نظام سياسي متكامل ومدعوم بقدرات اقتصادية ونظم اجتماعية راقية، فضلاً عن القوانين التي تضبط إيقاع تلك العلاقات، كل ذلك يبقى دائما على قيم ومعايير )كما اسلفنا(، بمعنى على هوية واضحة المعالم. يبقى الوطن الذي يعيش فيه الأفراد لا يحدد لهم نوع الهوية التي إليها ينتسبون، فالوطن الواحد قد يكون تعرض لتغييرات عديدة سوآءا على الأنظمة السياسية المختلفة أو المتناقضة، وهنا تكون الهوية هي العدسة التي من خلالها يحدد المواطنون ما هو مناسب أو غير مناسب، صالح كان أو غير صالح لوطنهم، فإذا اختلفت العدسات اختلف معها تقويم الناظرين إلى ما ينظرون أليه وأن اتفقوا على الحقائق الحسية. وعلى وفق هذا المنطق فإن المواطنين مهما كان إخلاصهم لوطنهم وحرصهم على مصلحته لا يمكن أن ينظروا إلى تلك المصلحة بوصفهم مواطنين فقط، بل لا بد أن ينظروا إليه بحسب هواياتهم. أذن لابد للمواطنين من هوية ومن ثقافة تكون هي المنظار الذي ينظرون به إلى الواقع والمعيار الذي يقترحون به الحلول لمشكلاتهم. والمواطنة في الوطن الواحد ستكون هشة إذا تعددت الهويات، وقد يؤدي ذلك إلى تمزيقه، وفي حالة إمكانية توحيد الهويات في الوطن الواحد يؤدي بالضرورة إلى بناء الوطن الواحد المتماسك والمواطنة الحقة، بمعنى أن المختلفون في الوطن الواحد بسبب تعدد الهويات يجب عليهم الاجتماع لتقرير مبدأ (أن مصلحتهم جميعا أن يبقوا في وطن واحد)، ثم ينظرون إلى الكيفية التي يحققون بها هذا الهدف، وعلى أساس فهمهم المعمق لحقيقة: (هذه أوضاعنا وهذه خلافاتنا فلنبحث عن حل أصيل لها ومتناسب معها وهو الحل الذي يستلزم بالضرورة قدر من التنازلات والمساومات). وسنتناول دراسة الموضوع من خلال مبحثين: الأول: المواطنة .. انتماء واندماج وطني. الثاني: الهوية خصوصية تاريخية وثقافية. ثم الخاتمة وقائمة الهوامش.
Keywords: قيم المواطنة -- الهوية الوطنية -- الانتماء الثقافي